Fulfillment Of The Right Of Justice When Persons With Disabilities Commit Criminal Acts - Febriyanti Bulo (Estudiante Law Journal, 2020)
This study aims to find out the fulfillment of the right to justice when people with disabilities commit criminal acts. The research method used is empirical research by conducting sample withdrawal using purposive sampling and data analysis using qualitative research approaches. The results showed that the fulfillment of the rights of persons with disabilities in the batucada police jurisdiction is less than optimal even though the police have carried out their role as law enforcement by carrying out the process of investigation and investigation on a person with disabilities as a criminal perpetrator. However, it has not been fully maximized in fulfilling the rights of justice of persons with disabilities themselves because it can be seen based on the data and information obtained that when persons with disabilities face the law, in this case, is a criminal offender, the police only focus on the use of regulations that are generally without being supported by special regulations, in this case, is law No. 8 of 2016 concerning Persons with Disabilities which explains  About the rights of a disabled person. Police, especially investigators, can better understand law number 8 of 2016 on persons with disabilities so that in the process of examination in the police the right to justice of a person with a disability can be more fulfilled as a whole.